2017
DOI: 10.2175/106143017x15051465918976
|View full text |Cite
|
Sign up to set email alerts
|

Landfill Leachate Treatment by Electrocoagulation and Fiber Filtration

Abstract: Landfilling is widely adopted as one of the most economical processes for solid waste disposal. At the same time, landfill leachate is also a great environmental concern owing to its complex composition and high concentrations of contaminants. This research investigated electrocoagulation and fiber filtration for the treatment of landfill leachate. Besides electrical current (i.e., current density) and reaction time, pH played a very important role in arsenic and phosphorus removal by electrocoagulation. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Several types of industrial wastewaters including pharmaceuticals, tannery and leather, textile, meat processing, fish, and marine products contain high concentrations of salts [6,7]. Salt can also be found at high concentrations in the leachate of urban landfill sites, contaminated groundwater, and the wastewaters resulting from mining operations and recycling units of gas and oil industries [[8], [9], [10]]. Fish processing industries need large amounts of sodium chloride for fish preservation.…”
Section: Methods Detailsmentioning
confidence: 99%
“…Several types of industrial wastewaters including pharmaceuticals, tannery and leather, textile, meat processing, fish, and marine products contain high concentrations of salts [6,7]. Salt can also be found at high concentrations in the leachate of urban landfill sites, contaminated groundwater, and the wastewaters resulting from mining operations and recycling units of gas and oil industries [[8], [9], [10]]. Fish processing industries need large amounts of sodium chloride for fish preservation.…”
Section: Methods Detailsmentioning
confidence: 99%
“…In previous studies, different physicochemical treatments have been tested in leachate, including membrane filtration (Costa et al, 2019), coagulationflocculation, flotation, adsorption, Fenton oxidation (Méndez et al, 2009;Aftab and Hur, 2019;Smaoui et al, 2019, Zhang et al, 2019, Fenton/coagulation (Wu et al, 2010;Luo et al, 2019), heterogeneous Fenton and electrofenton (Sruthi et al, 2018), electrocoagulation with fiber filtration (Li et al, 2017), electrofenton with different doses of H 2 O 2 and Fe 2+ (Mohajeri et al, 2019) and using of sodium sulphate with H 2 O 2 in an advanced oxidation process (Hilles et al, 2016), among others. However, there is no treatment or treatment set have been found that achieve satisfactory removal in leachates and residue generated that being disposed under the applied normativity and are also economically feasible.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigations have successfully applied EC to remove COD from a landfill leachate [1,2,[16][17][18]. In these studies, affecting parameters and their individual, and sometimes collective roles, in the enhancement of EC have been investigated.…”
Section: Introductionmentioning
confidence: 99%